Complete genome sequencing and construction of full-length infectious cDNA clone of papaya ringspot virus-HYD isolate and its efficient in planta expression - Gupta, Prodosh; Parupudi, Pavani L. C.; Supriya, Laha; Srivastava, Harshal; Padmaja, Gudipalli; Gopinath, Kodetham (Frontiers in Microbiology, 2023)
Papaya ringspot virus (PRSV) is a devastating Potyvirus that causes papaya ringspot disease in Carica papaya plantations globally. In this study, the complete genome sequence of a PRSV isolate from Shankarpalli, Telangana, India, was reported and designated as PRSV-HYD (KP743981.1). The genome is a single-stranded positive-sense RNA comprising 10,341 nucleotides. Phylogenetic analysis revealed that PRSV-HYD is closely related to PRSV Pune (Aundh) isolate with 92% and 95% nucleotide and amino acid sequence identity, respectively. To develop infectious cDNA (icDNA), the complete nucleotide sequence of PRSV-HYD was cloned between the right and left borders in the binary vector pCB301 using BglII and XmaI restriction sites. Cauliflower mosaic virus (CaMV) double promoter (35S) was fused at the 5′-end and Avocado sunblotch viroid (ASBVd) ribozyme (RZ) sequence was fused to the 3′ end to generate an authentic 3′ viral end in the transcribed mRNAs. The icDNA generated was mobilized into the Agrobacterium tumefaciens EHA 105, and the agrobacterial cultures were infiltrated into the natural host C. papaya and a non-host Nicotiana benthamiana plants; both did not show any symptoms. In RT-PCR analysis of RNAs isolated from N. benthamiana, we could detect viral genes as early as 3 days and continued up to 28 days post infiltration. Alternatively, virion particles were purified from agroinfiltrated N. benthamiana plants and introduced into C. papaya by mechanical inoculation as well as by pinprick method. In both cases, we could see visible systemic symptoms similar to that of wild type by 40 days. Additionally, we studied the expression patterns of the genes related to plant defense, transcription factors (TFs), and developmental aspects from both C. papaya and N. benthamiana.